Conditions for inducing T helper cells in vitro. - Kontiainen, S; Feldmann, M (1975)
Lymphoid cells of CBA mice were triggered to act as specific helper cells by incubation with protein antigen (usually keyhole limpet haemocyanin (KLH)) in Marbrook cultures in vitro. After optimum priming, these helper cells, at optimal numbers, stimulated B cells (from unprimed spleens) to respond to trinitrophenyl-KLH in vitro. The in vitro-induced helper cells were carrier-specific. B cell depletion before helper cell induction increased the efficiency of helper cell induction and thus provided further proof of the T-cell nature of in vitro helper cells. Heterogeneity within T helper cell precursors is suggested on the basis of differences in antigen dose requirements of precursor cells in cortisone-resistant thymocytes, spleen, or lymph nodes.